A black‐blood ultra‐short echo time (UTE) sequence for 3D isotropic resolution imaging of the lungs. Issue 6 (8th February 2019) - Delacoste, Jean; Feliciano, Helene; Yerly, Jérôme; Dunet, Vincent; Beigelman‐Aubry, Catherine; Ginami, Giulia; van Heeswijk, Ruud B.; Piccini, Davide; Stuber, Matthias; Sauty, Alain
Abstract : Purpose: Ultra‐short echo time MRI is a promising alternative to chest CT for cystic fibrosis patients. Black‐blood imaging in particular could help discern small‐sized anomalies, such as mucoid plugging, which may otherwise be confused with neighboring blood vessels, particularly when contrast agent is not used. We, therefore, implemented and tested an ultra‐short echo time sequence with black‐blood preparation. Additionally, this sequence may also be used to generate bright‐blood angiograms. Methods: Using this sequence, data was acquired during free breathing in 10 healthy volunteers to obtain respiratory‐motion‐resolved 3D volumes covering the entire thorax with an isotropic resolution of (1 mm) 3 . The magnitude of signal suppression relative to a bright‐blood reference acquisition was quantified and compared with that obtained with a turbo‐spin echo (TSE) acquisition. Bright‐blood angiograms were also generated by subtraction. Finally, an initial feasibility assessment was performed in 2 cystic fibrosis patients, and images were visually compared with contrast‐enhanced images and with CT data. Results: Black‐blood preparation significantly decreased the average normalized signal intensity in the vessel lumen (−66%; P < 0.001). Similarly, blood signal was significantly lowered (−60%; P = 0.001) compared with the TSE acquisition. In patients, mucoid plugging could be emphasized in the black‐blood datasets. An intercostal artery could also be visualized in the subtraction angiograms. Conclusion: Black‐blood free‐breathing ultra‐short echo time imaging was successfully implemented and motion‐resolved full volumetric coverage of the lungs with high spatial resolution was achieved, while obtaining an angiogram without contrast agent injection. Encouraging initial results in patients prompt further investigations in a larger cohort.